PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM MELINDUNGI TENAGA KERJA INDONESIA DI MALAYSIA TAHUN 2013-2015 - Fitri Andayani; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
International Organization for Migration (IOM) dedicated to promoting humane and orderly migration for the mutual benefit in the protection of Indonesian Workers (TKI) in Malaysia. IOM facilitated the development of policies and programs aimed at the good of migrants, communities, and provide effective protection to migrant families, these activities can help people who plan to work abroad. Behind the objectives and benefits, the placement of workers abroad have a negative effect. The laws that apply in the destination of migrant workers that do not provide protection. IOM has been working closely with the Indonesian government to support the ongoing efforts of government in the eradication of violence migrant workers in Malaysia.This article aims to explain the role of IOM in protecting Indonesian workers in Malaysia in 2013-2015, IOM's relief effort is a form of the Vision and Mission of IOM itself. The object of this study is the workers who are in Malaysia. The method used is qualitative and quantitatively by collecting data through books, journals, official publications and websites that are relevant to this study as well as direct interviews with stakeholders. Further use Pluralist perspective and role theory advanced by Mochtar Mas'oed.IOM organization does not work alone, but in collaboration with the BNP2TKI, it is characterized by Memorandum of Understanding (MOU). besides IOM also to give venture capital assistance to workers who have been deported.Keywords: IOM, migrant workers.